Green seduction : money, business, and the environment - Streever, Bill (University Press of Mississippi, 2007)
Bill Streever has worked in almost every camp involved with the environment. He is a scientist who has worked in both public and private sectors. He brings that wide experience and the perspective of many others like him to Green Seduction: Money, Business, and the Environment . Thirty-five years ago, polluted rivers burned, cities and farms dumped raw sewage into aquifers, highway and dam construction proceeded with little thought to environmental impact, and carcinogens and acids billowed from smokestacks. Today much has changed. Government jobs and university training programs exist in envi.